2008
DOI: 10.1016/j.drugalcdep.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid use, misuse, and diversion among street drug users in New York City

Abstract: POs are an important component of street drug users' drug-taking regimes, especially those who are Physically Ill Chemical Abusers (PICA). Future research is needed to model PO use, misuse, and diversion among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 12 publications
8
105
0
Order By: Relevance
“…It confirms a recent study in NYC that also indicated that, among street-recruited addicts, only 2.8% indicated having received methadone through a physician or pharmacy. (28) Not surprisingly, more methadone than buprenorphine was reportedly used outside of medical supervision. Buprenorphine has only been available in the U.S. since 2003 and early reports indicate that diversion of buprenorphine has not been widespread nor created significant public health problems when compared with other opioids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It confirms a recent study in NYC that also indicated that, among street-recruited addicts, only 2.8% indicated having received methadone through a physician or pharmacy. (28) Not surprisingly, more methadone than buprenorphine was reportedly used outside of medical supervision. Buprenorphine has only been available in the U.S. since 2003 and early reports indicate that diversion of buprenorphine has not been widespread nor created significant public health problems when compared with other opioids.…”
Section: Discussionmentioning
confidence: 99%
“…(9,26) Understanding methadone and buprenorphine diversion and its association with public health problems, as well as its connection with the drug abuse treatment process, is of considerable importance given the recent expansion of buprenorphine treatment in the U.S. and the sharp rise in methadone-related overdose deaths in the past few years. (27,28) Although there has been some recent epidemiological research concerning methadone diversion, (29) there has been limited ethnographic research since the work of Hunt and colleagues (30) more than two decades ago. Additionally, little is currently known regarding the uses of diverted buprenorphine or how it compares to the uses of diverted methadone.…”
mentioning
confidence: 99%
“…Available data suggest that ingestion (with or without manipulation of the prescribed formulation) is the most prevalent route of abuse of prescription opioid analgesics, followed by inhalation and injection. [6,11,[22][23][24][25][26][27][28][29][30][31] Comprehensive data on methods of manipulation and routes of abuse of prescription opioid analgesics have been generated through the US National Health and Wellness Survey. [31] The prevalence of prescription opioid analgesic abuse in the 3 months before the survey was estimated at 1.3% of the adult population in the USA.…”
Section: Frequency Of Different Routes Of Abusementioning
confidence: 99%
“…Reports of PO injection have risen worldwide, including in the United States (Davis and Johnson, 2008;Young et al, 2010;Surrat et al, 2011;Lankenau et al, 2012;Black et al, 2013;MateuGelabert et al, 2015), Europe (Partanen et al, 2009;Keijzer and Imbert., 2011;Roux et al, 2011), South Asia (Larance et al, 2011) and Australia (Degenhardt et al, 2006). In Canada, over the past decade, PO injection has gained in popularity among drug users across the country (UHRI, 2013; Leclerc et al, 2013;Firestone and Fischer, 2008;Roy et al, 2011;Roy et al, 2013;Bruneau et al, 2012;Fischer et al, 2006;PHAC, 2014).…”
Section: Introductionmentioning
confidence: 99%